2006
DOI: 10.1091/mbc.e05-06-0548
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear RNA-binding Protein Sam68 Translocates to the Cytoplasm and Associates with the Polysomes in Mouse Spermatocytes

Abstract: Translational control plays a crucial role during gametogenesis in organisms as different as worms and mammals. Mouse knockout models have highlighted the essential function of many RNA-binding proteins during spermatogenesis. Herein we have investigated the expression and function during mammalian male meiosis of Sam68, an RNA-binding protein implicated in several aspects of RNA metabolism. Sam68 expression and localization within the cells is stage specific: it is expressed in the nucleus of spermatogonia, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 53 publications
4
97
0
Order By: Relevance
“…This observation suggests a possible additional function of Sam68 in highly malignant cancer cells. Indeed, it was previously shown that Sam68 localizes in the cytoplasm of male germ cells (Paronetto et al 2006) and neurons (Grange et al 2004), where it associates with the translation initiation complex ) and with polysomes (Grange et al 2004, Paronetto et al 2006, thereby regulating translation of selected mRNAs (Grange et al 2009. Importantly, the translational activity of Sam68 in male germ cells was also stimulated by the RAS/MAPK pathway (Paronetto et al 2006.…”
Section: Role Of Sam68 In Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…This observation suggests a possible additional function of Sam68 in highly malignant cancer cells. Indeed, it was previously shown that Sam68 localizes in the cytoplasm of male germ cells (Paronetto et al 2006) and neurons (Grange et al 2004), where it associates with the translation initiation complex ) and with polysomes (Grange et al 2004, Paronetto et al 2006, thereby regulating translation of selected mRNAs (Grange et al 2009. Importantly, the translational activity of Sam68 in male germ cells was also stimulated by the RAS/MAPK pathway (Paronetto et al 2006.…”
Section: Role Of Sam68 In Cancermentioning
confidence: 98%
“…Indeed, it was previously shown that Sam68 localizes in the cytoplasm of male germ cells (Paronetto et al 2006) and neurons (Grange et al 2004), where it associates with the translation initiation complex ) and with polysomes (Grange et al 2004, Paronetto et al 2006, thereby regulating translation of selected mRNAs (Grange et al 2009. Importantly, the translational activity of Sam68 in male germ cells was also stimulated by the RAS/MAPK pathway (Paronetto et al 2006. Thus, in addition to its well documented ability to modulate cancer-specific splicing events (Matter et al 2002, 2010, it is plausible to speculate that Endocrine-Related Cancer (2011) 18 R91-R102 www.endocrinology-journals.org cytoplasmic localization of Sam68 in advanced stages of tumors might contribute to neoplastic transformation by enhancing translation of specific mRNAs.…”
Section: Role Of Sam68 In Cancermentioning
confidence: 99%
“…PSF, for example, is a splicing regulator that associates with the androgen receptor and regulates its transcriptional activity, 46 similar to SAM68, 21 whereas the translation initiation factor eIF3 and the ribosomal proteins L7, S3, S4 and S7 might be involved in the mechanism of SAM68-dependent regulation of mRNA translation. [26][27][28] In this work, we have focused our attention on SND1 (Figure 1a), a transcriptional regulator that is also implicated in mRNA processing. 36,37 First, by comparing its expression levels in PCa cells (LNCaP and PC3) with respect to cells derived from a benign prostate hyperplasia (BPH1), we found that SND1 was expressed at higher levels in PCa cells, similar to SAM68 (Figure 1c).…”
Section: Identification Of Snd1 As a Novel Sam68-interacting Proteinmentioning
confidence: 99%
“…17 SAM68 is involved in regulating several aspects of RNA processing, such as transcription, [18][19][20][21] AS [22][23][24][25] and translation of cellular mRNAs. [26][27][28] Moreover, SAM68 displays pro-oncogenic functions and is frequently upregulated in human cancer types, 17 including prostate cancer (PCa), wherein it supports cell proliferation and survival to genotoxic stresses. 29,30 In spite of the increasing number of studies reporting a role of SAM68 in human cancer, 17,31 the mechanism(s) of action of this protein in neoplastic cells is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SAM68, GRTH and MILI, for instance promote translation of germ cell mRNA, while MSY2, MVH and NANOS2 act as inhibitors [6,142,145,146,[164][165][166][167]. As a result, the balance of proteins promoting and inhibiting translation is crucial to germ cell function.…”
Section: Rna Regulation In the Male Germlinementioning
confidence: 99%